MENUMBUHKAN JIWA ENTREPRENEUR UNTUK MENINGKATKAN PENDAPATAN PADA ANGGOTA RUMAH BACA JAKOSE MELALUI BISNIS MODEL CANVAS (BMC) (LPPM Universitas Dinamika Bangsa, 2023)
The importance of resources, especially financial, in social organizations is especially felt by one of the social organizations, namely the jakose reading house (Jambi Kota opposite) where in carrying out activities there must be funds that must be spent so that activities run smoothly. Therefore, with this training it is hoped that the members of the jakose reading house can increase their entrepreneurial spirit and express and create their business ideas through the Canva business model, which is related to easy use, it is hoped that the members of the jakose reading house will be able to so businesses that provide income for their operations or social activities will later be generated through training